Back to the revolution: the 1974 Portuguese spring and its 'austere anniversary' - Accornero, G. (2015)
The 40th anniversary of the Portuguese revolution took place in 2014 in a context of deep social and economic crisis. In common with Greek, Spanish, and to an extent, Italian citizens, the Portuguese had suffered, in the previous three years, from the imposition of drastic austerity measures of fiscal contraction. These measures, aside from worsening the economic situation and increasing unemployment, have deeply undermined what in the country are considered the “conquests” of the 25 April 1974 revolution that ushered in Portugal’s democracy – a set of social rights in terms of labour law, healthcare and access to education. As in other countries, these conditions have not gone unchallenged by civil society, and there has been an intensification of protest. If the “conquests of April” seem to be targeted in particular by the austerity measures, references to the revolution have returned to be a constant element in the contestation of the “troika’s” impositions.